Acceleration of Fracture Healing in Experimental Model: Platelet-Rich Fibrin or Hyaluronic Acid?. Issue 7 (October 2018) - Akyildiz, Servet; Soluk-Tekkesin, Merva; Keskin-Yalcin, Basak; Unsal, Gurkan; Ozel Yildiz, Sevda; Ozcan, Ilknur; Cakarer, Sirmahan
Abstract : Abstract: In this study, we compared the bone-healing effects of the local application of platelet-rich fibrin (PRF) and hyaluronic acid (HA) to bilateral tibial fractures in rats. Twenty-three adult male Sprague-Dawley rats were used. Twenty-two animals were randomly allocated to a control group (n = 6) and 2 study groups: PRF (n = 8) and HA (n = 8). The 23rd rat was used as a donor to obtain PRF. Each group was divided into 2 subgroups for histomorphometric and radiologic assessments at 2 and 6 weeks. Foreign body reaction, necrosis, inflammation, new bone formation, and fibrosis were investigated as bone healing parameters in terms of histopathologic analysis. The difference between the groups for these parameters was evaluated. The radiologic evaluation was performed by comparing the 3-dimensional reconstruction images of the fracture sites between the study and control groups. Histomorphometric evaluation showed that at 2 weeks postoperatively, the control group showed lesser bone formation (26.1 ± 6.6%) when compared to the study (HA: 54.7 ± 9.7%; PRF: 75.3 ± 19.2%) groups and PRF group showed highest total ossification. At 6 weeks postoperatively the PRF group showed lesser total ossification (50.7 ± 28.2%) when compared to control (76.3 ± 21.7%) and HA group. The HA (88.8 ± 13.3%) showed highest total ossification. In the control group, fibrosis was more prominent at week 6, whereas in the HA and PRF groups the amount of ossification increased. In contrast to histopathologic healing, radiologic bone healing did not differ significantly among the study and control groups 2 weeks after surgery, whereas at 6 weeks, the results of radiologic bone formation were in accordance with those of histopathologic bone healing.